CONCEPTUAL APPROACH TO AN AYURVEDIC AND MODERN SUTURE MATERIALS - Viraktamath Pallavi; Jalawadi Poornima; Aradhyamath Siddayya (International Journal of Applied Ayurved Research, 2022)
Acharya sushutha is knows as father of surgery and father of plastic surgery even till the date. Acharya sushruta described about various wound closer techniques along with suture materials, needles even though elaborative suturing procedure and their post wound management. Not only wound management but also various surgeries by using Astavidha Shastra karma and Seevana(suturing) is one among them. The success of all surgery depends on better wound healing. This will be achieved by suturing. Acharya Sushruta described in detail about Seevana(suturing) in his time period. Here an attempt is made throw light on Sushruta’s concept of Seevana Karma and modern suturing aspects.